Doing Good and Feeling Good Among African Americans: Subjective Religiosity, Helping, and Satisfaction. (August 2013) - Grayman-Simpson, Nyasha; Mattis, Jacqueline S.
Previous studies of religion's role in the connection between helping and well-being among African Americans have examined this relationship from a stress and coping theoretical standpoint, perpetuating a deficit model of positive functioning. In an effort to develop the literature, the authors approached the study of these relationships from a role identity theoretical standpoint, and a fulfillment perspective within a community sample of African American adults ( N = 140). Consistent with tests for mediation, the authors found support for the following: (1) helping positively predicted satisfaction, (2) subjective religiosity positively predicted helping, (3) subjective religiosity positively predicted satisfaction, and (4) the strength of the relationship between subjective religiosity and satisfaction was significantly reduced in the presence of helping. Findings point to a mediation effect for subjective religiosity and to role identity theory as a viable explanation for religion's role in the relationship between helping and well-being among African Americans.